The railways of England North Western. Midland. Great Northern. Manchester, Sheffield, and Lincoln. North Eastern. South Western. Great Western. Great Eastern. Brighton and South Coast. Chatham and Dover. South Eastern - Acworth, W. M. 1850-1925 (John Murray, 1890)
This title deals only with railways terminating in London, and seeks to highlight the positive aspects of each line described, rather than concentrating on defects.